HUBUNGAN PENGETAHUAN TERHADAP KEPATUHAN PERAWAT DALAM PERAWATAN PASIEN DENGAN VARISES ESOFAGUS GASTRODUODENUM POST LIGASI DI RSCM JAKARTA - Lubis, Erika; Dewi, Aliana; Nurjanah, Lincah (Faculty of Nursing and Midwifery, Binawan University, 2023)
Esophageal varices are dilated, tortuous veins that are usually found in the submucosa of the lower esophagus. Esophageal varicose veins can be life threatening if they do not get the right treatment so nurses are expected to have the knowledge to provide nursing care. Knowledge of nurse compliance in the care of patients with esophageal varices not only prevents bleeding but also increases the speed of patient recovery. The purpose of this study was to determine the relationship between knowledge and nurse compliance in the care of patients with gastroduodenal varicose veins post ligation at RSCM. The design of this research is descriptive quantitative which uses correlation analysis design with cross-sectional approach. The sample is 44 respondents. Analysis of statistical tests using the Chi Square test. The results showed that the majority of nurses were aged 25-35 years (63.6%), female (68.2%), D3 education (65.9%), working length of 3-5 years (43.2%) adequate knowledge ( 45.5%) obedient nurses (68.2%). There is a relationship between knowledge and nurse compliance in the care of patients with gastro-duodenal varicose veins ligation with p value: 0.001 means p<α where value: 0.05. It is hoped that nursing services can facilitate efforts to increase nurses' knowledge regarding the care of patients with esophageal varices gastro duodenal ligation, so as to improve nurse compliance in the care of patients with esophageal varices gastro duodenal ligation and create SOPs for the care of patients with esophageal varices gastro duodenal ligation that must be known by all the nurses in the room.